2008
DOI: 10.5194/acp-8-3411-2008
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the tropopause layer and lower stratosphere above a tropical cyclone: a case study on cyclone Davina (1999)

Abstract: Abstract. During the APE-THESEO mission in the Indian Ocean the Myasishchev Design Bureau stratospheric research aircraft M55 Geophysica performed a flight over and within the inner core region of tropical cyclone Davina. Measurements of total water, water vapour, temperature, aerosol backscattering, ozone and tracers were made and are discussed here in comparison with the averages of those quantities acquired during the campaign time frame.Temperature anomalies in the tropical tropopause layer (TTL), warmer t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 68 publications
5
41
0
Order By: Relevance
“…The tropical cyclones (TCs) are severe weather events often leading to deep convective activity and persisting for long time. They alter the physics and chemistry of the TTL and they play a fundamental role on the atmospheric circulation and troposphere-stratosphere exchange (Ray and Rosenlof, 2007;Cairo et al, 2008;Fueglistaler et al, 2009;Romps and Kuang, 2009). The GPS Radio Occultation (RO) technique (Kursinki et al, 1997) is useful to study severe weather phenomena because the GPS signal is independent on the weather conditions and it allows profiling atmospheric parameters with high vertical resolution and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The tropical cyclones (TCs) are severe weather events often leading to deep convective activity and persisting for long time. They alter the physics and chemistry of the TTL and they play a fundamental role on the atmospheric circulation and troposphere-stratosphere exchange (Ray and Rosenlof, 2007;Cairo et al, 2008;Fueglistaler et al, 2009;Romps and Kuang, 2009). The GPS Radio Occultation (RO) technique (Kursinki et al, 1997) is useful to study severe weather phenomena because the GPS signal is independent on the weather conditions and it allows profiling atmospheric parameters with high vertical resolution and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The increased ozone levels in the boundary layer as well as the near surface by as much as 20 to 30 ppbv due to strong downward transport of ozone in the tropical convection is also observed (Betts et al, 2002;Sahu and Lal, 2006;Grant et al, 2008). Cairo et al (2008) reported that the colder temperatures are observed in the tropical tropopause layer (TTL) region during Cyclone Davina and also reported on the impact of the TCs on the UTLS structure and dynamics at a regional scale. A detailed review on the effect of TCs on the UTLS can be found in same report.…”
Section: Introductionmentioning
confidence: 95%
“…Deep convection in typhoons (or tropical cyclones) provides a preferred condition for stratosphere-troposphere exchange [1,2] that causes the variability of ozone in the upper troposphere and lower stratosphere. The injection of tropospheric ozone-poor air into the lower stratosphere near the typhoon's eye has been observed based on the aircraft measurements [3][4][5][6][7] and satellite data [8][9][10][11]. Moreover, stratospheric ozone-rich air intrusion into the troposphere due to the subsidence in the eye of typhoons has been reported [3,5,12,13].…”
mentioning
confidence: 98%
“…These typhoon-related ozone episodes are generally believed to be the results of tropospheric air upwelled by deep convection and ozone-rich stratospheric air downwelled by intrusion [6,8,10,13]. Although there are discrepancies between the total column ozone derived from satellites and aircraft observations in typhoons' eyes [7,12], the regions of high column ozone inside the eye regions are observed during intense stages of typhoons [6]. Additionally, typhoon not only influences the local ozone budget, but also has an impact on the ozone meridional transport [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation